Annual review in an adolescent diabetes clinic: process, outcomes and relationship to early glycemic control and attendance rates. (29th September 2015) - Sachdev, P; Garbe, F; Scott, A; Price, K
Abstract : Background: During the transition period to adult care, there is a risk of deteriorating control, development of complications and loss from service. Ensuring appropriate annual review is hampered by poor attendance rates. Various models of care exist with a period of shared care being suggested as the most popular and effective. Young people between 15–20 years attend our transition clinic which is staffed jointly by the paediatric and adult teams providing continuity of care. The aim of this audit was to assess our outcomes in terms of the annual review process, the prevalence of complications and their relationship to attendance and long-term glycemic control. Aims: 1) Audit of the annual review process in our transition clinic 2) Correlation between complication rates and (a) Haemoglobin A1c (HBA1c) at diagnosis, point of transfer and current average (b) Duration of diabetes (c) Attendance rates Methods: Retrospective review of case notes. Results: Case notes of 69 patients (38 girls) out of 115 reviewed. Mean age 17.6 years, duration of diabetes 1–18 years (mean 8.9 years). Mean and median HBA1c at point of transfer were 8.8% and 8.9%, respectively. Current mean and median HBA1c were 9.7% and 9.1%. Annual eye screening carried out for 72% with background retinopathy in 12%. Blood pressure measured for 93% of patients with 15.6% noted to be hypertensive. Albumin creatinine ratio available for 84% with proteinuria in 12%. Both complications noted in 8.5% of our group. Foot/shoe check carried out in 46% with no abnormalities identified. At least one appointment was missed by 70% of our patients over the last 1 year with 33% having missed two or more appointments. There was no significant difference between the group with complications and those without in terms of their HBA1c at diagnosis, at point of transfer and current values, their duration of diabetes and attendance rates. There was no evidence of tracking of HBA1c. Conclusions: Despite a good model of care, we are still failing to meet the needs of our adolescents in terms of glycemic control and willingness to attend clinic. Innovative ways of delivering care are needed to pave the way for effective transition.